2019
DOI: 10.1016/j.bmc.2019.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Natural product-inspired profluorophores for imaging NQO1 activity in tumour tissues

Abstract: Herein we designed a collection of trimethyl-lock quinone profluorophores as activity-based probes for imaging NAD(P)H:quinone oxidoreductase (NQO1) in cancer cells and tumour tissues. Profluorophores were prepared via synthetic routes from naturally-occurring quinones and characterised in vitro using recombinant enzymes, to be further validated in cells and fresh frozen canine tumour tissues as potential new tools for cancer detection and imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The phenazine form of the triazole compounds and quinones described in groups 1 and 3 were also evaluated in group 5 [94][95][96][97]. Group 6 is the most complete and diverse group addressed in this study, containing approximately two hundred 1,4naphthoquinones with broad substitution patterns in the benzenoid A-ring and B-ring.…”
Section: Assembly Of a Chemical Library For Virtual Screening Against Mpromentioning
confidence: 99%
“…The phenazine form of the triazole compounds and quinones described in groups 1 and 3 were also evaluated in group 5 [94][95][96][97]. Group 6 is the most complete and diverse group addressed in this study, containing approximately two hundred 1,4naphthoquinones with broad substitution patterns in the benzenoid A-ring and B-ring.…”
Section: Assembly Of a Chemical Library For Virtual Screening Against Mpromentioning
confidence: 99%
“…In the same year, Marc Vendrell and coworkers designed a new class of heterocyclic compounds for the detection of NQO1 activity in tumor tissues. [34] Probe 18 (Figure 11) was developed and designed by combining nitrogen-containing fluorescent heterocycles with trimethyl-locked quinone propionate groups. [35] It was used to detect fresh frozen dog samples of healthy and adenocarcinoma colon, and showed that tumor tissue exhibited brighter green fluorescence than healthy tissue.…”
Section: Quinone Oxidoreductase (Nqo1) Fluorescent Probementioning
confidence: 99%
“…It is a potential to be as practical tool for the early detection and diagnosis of cancer. In the same year, Marc Vendrell and coworkers designed a new class of heterocyclic compounds for the detection of NQO1 activity in tumor tissues [34] . Probe 18 (Figure 11) was developed and designed by combining nitrogen‐containing fluorescent heterocycles with trimethyl‐locked quinone propionate groups [35] .…”
Section: Quinone Oxidoreductase (Nqo1) Fluorescent Probementioning
confidence: 99%
“…The missing references are listed below as ref. [1][2][3][4][5][6], and should be cited in the original paper at the end of the following sentence on page 26729:…”
mentioning
confidence: 99%
“…Herein, we designed and synthesized a novel uorescent probe 1 for detection of hNQO1 based on TCF-OH as a chromophore and quinone propionic acid (QPA) as a recognition group. [1][2][3][4][5][6] The authors sincerely apologise for this oversight. The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers.…”
mentioning
confidence: 99%